Strategic Supply Chain Management - Khan, Syed Abdul Rehman; Yu, Zhang (EAI/Springer Innovations in Communication and Computing,, 2019)
This book covers the scope of supply chain and logistics, which has continued to grow with a rapid speed. The book includes core aspects of supply chain and logistics philosophy and practice. The authors then cover the general principles of supply chain and logistics that can be applied in countries throughout the world. Where concepts cannot be generalized, they are based primarily on a European model. The authors have also added some international material and examples from China, Pakistan, India, and the USA. The book is intended to help in the quest of supply chain and logistics to reduce cost and improve service, as well as to keep up-to-date the different facets of supply chain and logistics in a global market. In addition, this book helps candidates to who are undertaking examinations for universities and professional institutes, and bachelor and master students who are studying for degrees in supply chain management. In addition, the book covers technical terminologies, definitions, and a supply chain dictionary. Provides a comprehensive treatment of the global supply chain field for academics, students, and professionals; Includes relevant formulas of supply chain management and their explanations; Covers numerical problems, case studies, and discussion questions at the end of each chapter for readers to do self-assessment. .